Catalytic Hydrothermal Liquefaction of Artichoke Residues (Cynara Scolymus L.) to Valuable Chemicals - Levent Ballice; Mithat Yüksel; Mehmet Sağlam; Dilek Selvi Gökkaya (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Lignocellulosic biomass is accepted to be one of the best sustainable alternatives for overcoming fossil fuel dependence and to reduce environmental pollution. Intensive research studies have been carried out on conversion of this big potential source via chemical and biochemical processes to miscellaneous chemicals. According to one of the present methods of chemical conversion, cellulose and hemicellulose parts of the plant biomass can be converted to platform chemicals by hydrolysis, dehydration and rehydration reactions in the presence of acidic medium. In this study, the efficient conversion conditions of the Artichoke (Cynara Scolymus L.) leaves and stalks to the valuable chemicals (formic acid, acetic acid and 5-hydroxymetilfurfural) were investigated using acid (HCl, HNO3 and H2SO4) catalyzed hydrothermal reaction. Experiments were performed in the temperature range of 150°C - 300°C and at the pH values 2.0 - 3.0 with a reaction time of 1 hour. Evolution of liquid parts and their variations with respect to reaction parameters were determined using HPLC via related analysis